A cross sectional study to find out the health seeking behaviour of brick kiln workers - Kazi, Rufiat; Bote, Mangala M. (International Journal Of Community Medicine And Public Health, 2018)
Background: This study was designed to assess the factors associated with the health seeking behaviour of brick kiln workers and to acquire an in depth understanding of their health. Methods: 420 brick kiln workers who were eligible for the study were interviewed using a semi structured, pre-designed, pre-tested interviewer administered questionnaire. Statistical analysis used: SPSS version 20. Results: 48.9% showed good health seeking behavior while 51.1% showed poor health seeking behavior. 69.4% more than 40 years, 38.2% in the age group of 26-40 years and 40.2% in the age group of 18-25 years showed good health seeking behaviour. Conclusions: Good health seeking behavior was seen in older age groups, females and bigaaris.